2020
DOI: 10.1002/agt2.6
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly and tunable optical properties of intramolecular charge transfer molecules

Abstract: Crystalline aggregates formed by self‐assembly of organic small molecules have aroused intensive attention in many fields due to their controllable morphologies and functionalization. The advantages of intramolecular charge transfer (ICT) compounds endow them with the ability to self‐assemble into diverse dimensional crystalline microstructures, as potential candidates for advanced materials and smart miniatures in practical applications. In this review, the recent progresses of self‐assembled microstructures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Researchers have established many photophysical theories based on molecular science, which focus on the fluorescent mechanisms of organic fluorophores. For example, efficient fluorophores are closely correlated with large π conjugation through covalent bonds (e.g., double bond, triple bond, or aromatic ring), , and introduction of donor (D) and acceptor (A) groups into the molecular skeleton often leads to redder but weaker emission, , especially for molecules showing twisted intramolecular charge transfer effects. , In most cases, these molecular theories are capable of revealing the photophysical mechanisms of organic luminescent materials. Based on these studies at the molecular level, a paradigm of material research is gradually formed that molecular structures and properties always determine the performance of macroscopic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have established many photophysical theories based on molecular science, which focus on the fluorescent mechanisms of organic fluorophores. For example, efficient fluorophores are closely correlated with large π conjugation through covalent bonds (e.g., double bond, triple bond, or aromatic ring), , and introduction of donor (D) and acceptor (A) groups into the molecular skeleton often leads to redder but weaker emission, , especially for molecules showing twisted intramolecular charge transfer effects. , In most cases, these molecular theories are capable of revealing the photophysical mechanisms of organic luminescent materials. Based on these studies at the molecular level, a paradigm of material research is gradually formed that molecular structures and properties always determine the performance of macroscopic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[8,26,[40][41][42][43][44][45] The optimization of the NLO response of organic materials usually involves the introduction of electron donating and accepting groups into a π-conjugated molecule. [19,[46][47][48] By chemically optimizing the electronic structures of the electron donors (D) and acceptors (A) as well as the π-bridges, intramolecular charge transfer (ICT) processes within these D-π-A molecules are facilitated and consequently, their NLO hyperpolarizabilities are boosted. [49,50] However, such an optimization of the molecular hyperpolarizabilities does not always lead to materials with high macroscopic NLO susceptibilities, because such D-π-A molecules have a strong tendency to self-organize in centrosymmetric ways, driven by dipole-dipole interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing the strength of the electron-donating and electron-withdrawing abilities between a D-A pair, the emission from the CT state becomes dominant without any LE feature. 52,53 Specifically, polychromic emission from CT states may be observed if two or more different D-A pairs are presented. Chi et al reported an asymmetrical compound CPzPO based on diphenylsulfone, diphenylketone, and diphenylphosphine oxide, which showed a donor-acceptor-acceptor conformation [Fig.…”
Section: Dual Fluorescence From Two Statesmentioning
confidence: 99%